HIPEC plus EPIC paclitaxel for maximal perioperative treatments of advanced epithelial ovarian cancer. Long-term results of a pilot study. (December 2020) - Sugarbaker, Paul H.; Stuart, O. Anthony
Abstract: Background: A unique time in which to effectively treat an intraabdominal malignancy is the time at which the surgeon attempts complete removal of the malignant process. Although surgery is effective for visible disease, micrometastases or multiple small cancer nodules are not amenable to resection. Alternative interventions to deal with residual disease disseminated on peritoneal surfaces are needed. Materials and methods: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) can be combined with early postoperative intraperitoneal chemotherapy (EPIC) in order to maximally treat gross disease within the abdomen and pelvis and also the minimal residual disease that exists in many patients after resection. The third component of this treatment for ovarian malignancy was EPIC paclitaxel in this study. The clinical features, pharmacologic assessments, and survival were determined in ovarian cancer patients in whom EPIC was added to the perioperative treatment plan. Results: Patients with high grade serous ovarian cancer underwent CRS, HIPEC with cisplatin/doxorubicin, and EPIC paclitaxel. These treatments combined as a single intervention were studied in 10 patients. The median number of peritonectomy procedures was 1, the median number of visceral resections was 5, and the median time required in the operating room was 8 h. Two patients had a class 3 adverse event. The median survival of patients was 50 months. Pharmacokinetic analysis of the intraperitoneal paclitaxel showed 252 ± 153 times exposure of peritoneal surfaces as compared to intravenous exposure when the drug was instilled into the peritoneal space. Conclusions: EPIC paclitaxel was successfully combined with CRS and HIPEC in 10 patients with ovarian cancer. The treatment was tolerated approximately the same as other major cytoreductive surgical procedures for ovarian cancer or other malignancies. Survival of these ovarian cancer patients seemed unusually prolonged as compared to other patients with stage 3b or recurrent disease. In this pilot study CRS, HIPEC and EPIC were safe and effective. Highlights: Ovarian cancer is an aggressive disease process that has multiple treatment options. The disease progresses in its early stages exclusively within the peritoneal space. Aggressive surgery, HIPEC and EPIC paclitaxel was performed in 10 patients. Pharmacokinetic studies of intraperitoneal paclitaxel suggests benefit. For peritoneal metastases, intraperitoneal paclitaxel should be systematically studied.